Investigating the Effects of Subchronic Sesame and Flaxseed Oils Consumption against Seizure and Depression in Adult Male Mice: Effects of Sesame and Flaxseed oils against seizure and depression - Zalkhani, Raha; Moazedi, Ahmad Ali; Najafzadehvarzi, Hossein (Iranian Journal of Pharmaceutical Sciences, 2020)
Epilepsy is a highly debilitating disorder by unpredictable seizures associated with emotional disturbance.One potential treatment for seizure and depression is dietary therapy. So, this study evaluated effects of daily oral administration of sesame and flaxseed oils in depression and seizure. Twenty-one adult male mice were divided into the following groups: control (normal saline recipient, 1ml/kg( , sesame and flaxseed oils groups (8ml/kg bodyweight, for 21 days). At the 22nd day, locomotor activity and depressive - like behavior were assessed by open field and tail suspension tests. Also in 23rd day, animals received a subcutaneous injection of strychnine for induction of seizure. The seizure latency and death time were recorded through observation of animal behavior immediately after injection of strychnine. There were no significant differences in locomotor activity among control, sesame and flaxeed groups. But it has been shown a significant increase in latency to immobility (p=0.027) and decrease in total immobility (p=0.001) in flaxseed oil group compared to control group. Also sesame oil group showed a significant reduction in the duration of total immobility (p=0.027) and its latency to immobility wasn’t significant. There were no significant differences in latency to seizure and death time in flaxseed oil groups compared to the control group. The subchronic consumption of sesame oil significantly increased the death time than the control group (p=0.04) but the latency to seizure was not significant. The results reveal that sesame and flaxseed may be considered as a food adjuvant for attenuating emotional problems in epilepsy.